Pengembangan Media Pembelajaran Anak Playgroup dan Taman Kanak- kanak Berbasis Web - Ariyanti, Renita Sriyuni; , Prof. Dr. Budi Murtiyasa, M.Kom (2016)
The quality of education is still to low in a study that only uses books and monotonically sometimes for very small children will feel bored and will inevitably result interest in learning, the learning interest of early childhood education such as Play Group / kindergarten (PG / TK) is what will be brought up to adults. With the development of information technology is now almost all ages use it so that it can improve the performance of fast and satisfactory outcome. For this reason, the need to develop new learning media that can attract interest in learning in early childhood. The results of this study in the form of the introduction of the senses, alphabet letters, numbers, and colors. This is expected to increase rnotivasi learn the lesson aims to develop systems based instructional design websites using PHP and MYSQL.